Restoration of liver function in malnourished mice orally administered with Pleurotus ostreatus fruiting bodies extract - Gabriel Llauradó; Yaixa Beltrán; Humberto J. Morris; Ebert Marcos; Usnavia Díaz; Jane Marcos; Jesús García; Dunilka Disotuar; Paul Cos (Journal of Pharmacy & Pharmacognosy Research, 2020)
Context: Malnutrition is considered worldwide as an important burden because it provokes serious damage in several physiological and metabolic mechanisms, among them the hepatic function. Currently, natural products are being used to reduce the negative impact of some pathological disorders in liver. Pleurotus genus of edible mushrooms has shown a wide spectrum of medicinal effects, but its role in the management of liver complications associated to malnutrition is not clear.